North American Indian Travelling College performance
Title based on content of image. Caption on verso reads: "North American Indian Traveling College" The North American Indian Traveling College is now known as the Native North American Traveling College. Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada.